Analysis of Income and Value-Added of Spinach Processed Product in Payakumbuh City (Case Study in Alfin Spinach Chips Home Industry) - Ulda Yanti Surmila; Mega Amelia Putri (Department of Agribusiness, Halu Oleo University, 2022)
Spinach is one of the most popular types of vegetables in Indonesia. The increasing public demand for spinach has increased the creation of processed products made from spinach, one of which is spinach chips. Keripik Bayam Alfin is one of the home industries that process spinach into spinach chips but has never analyzed the value-added of its industry. This research aims to determine the production process of spinach chips, find out the value-added to making spinach chips, and know the income of the spinach chips home industry. And to find out whether spinach chips can be a promising alternative source of the economy in Payakumbuh or not. This research was implemented on Friday, December 26th, 2021, at the Alfin Spinach Chips Home Industry in Payolansek Village, RT 001 RW 003, West Payakumbuh District Payakumbuh City, West Sumatra Province. The method used is the value-added analysis method by Hayami. Respondents in this study were the owner and workers in the production sector. Based on the research, the amount of money received per production is IDR910.000, and the income earned per production is IDR249.791. The value-added was IDR9.725/kg. So this home industry has an excellent prospect to be used as a promising alternative source of the economy.